The complete mitochondrial genome of Gonepteryx mahaguru (Lepidoptera: Pieridae). (3rd March 2016) - Yang, Jianing; Xu, Chang; Li, Jialian; Lei, Ying; Fan, Cheng; Gao, Yuan; Xu, Chongren; Wang, Rongjiang
Abstract: The complete mitochondrial genome of Gonepteryx mahaguru (Lepidoptera: Pieridae) is 15, 221 bp in length, containing 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), 2 ribosomal RNA genes (LrRNA and SrRNA) and 1 non-coding A + T-rich region. The nucleotide composition is significantly biased toward A + T (80.9%). All PCGs are initiated by classical ATN codon, with the exception of COI, which begins with TTA codon. Nine PCGs harbor the complete stop codon TAA, whereas COI, COII, ND4 and ND5 stop with incomplete codons, single T or TA. All tRNAs can be folded into the typical cloverleaf secondary structure, except for tRNA Ser (AGN). The A + T content of AT-rich region is 95.2%, same to the highest one in the known species in Pieridae.